A diasporic right to the city: the production of a Moroccan diaspora space in Granada, Spain. (24th July 2019) - Finlay, Robin
Abstract: In this paper, I bring together ideas of 'diaspora space' and 'the right to the city' and empirically demonstrate how the formation of diasporas is frequently dependent on migrants attaining certain rights to the city. These rights, I argue, are conditioned and attained by the interplay of urban structural context with the place-making strategies of migrants. Drawing on 8 months of ethnographic fieldwork, I demonstrate that Moroccan migrants in Granada, Spain, have achieved a partial right to a neighbourhood of the city, producing a multi-sensory, self-orientalised diaspora space. First, I show that certain urban conditions in Granada provided a foothold for Moroccan migrants to begin to form a diaspora and transform urban space. Second, I demonstrate that through the mobilisation of a strategically self-orientalised cultural capital, the diaspora have partly appropriated the valuable history of Al-Andalus, a key component in the city's tourist imagery. These factors and strategies have enabled Moroccan migrants to gain a right to have a visible presence in the city, a right to produce and transform urban space and a right to spatalise diverse identities – all key rights, I argue, in the formation of a diaspora.